REDEFINING ESP: BRIDGING THE GAP BETWEEN TRADITIONAL METHODS AND MODERN EDUCATIONAL NEEDS - Sakti, Nur Sri Sakti; Sarkiah, Sarkiah; Sukma, Sukma; Amaluddin, Amaluddin; Efendi, Rahman (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2024)
This literature review explores the evolving landscape of English for Specific Purposes (ESP) and examines how traditional methods can be integrated with modern educational needs to enhance language instruction. Initially, ESP focused on specialized vocabulary and discourse practices within specific professional fields, relying heavily on textbook-based instruction and rigid methodologies. These traditional approaches, while foundational, have been critiqued for their limited flexibility, engagement, and broader communicative development. Recent advancements in educational technology have introduced new opportunities for ESP, including interactive learning platforms, personalized instruction, and increased accessibility. These innovations address several limitations of traditional ESP methods by making learning more engaging and adaptable to diverse learner needs. The review highlights the benefits of integrating technology into ESP instruction, such as enhanced student engagement and personalized learning experiences. To bridge the gap between traditional and modern approaches, a balanced method combining face-to-face instruction with digital tools is proposed. Blended learning models and collaborative online platforms offer a more holistic and effective ESP education. However, challenges such as resource constraints, digital literacy, and appropriate assessment methods remain. The review concludes by emphasizing the importance of adopting a balanced approach that incorporates both traditional and modern methods to meet the evolving needs of ESP learners. Future research should focus on overcoming existing challenges and developing innovative solutions to further enhance ESP instruction in a rapidly changing educational environment. Keywords: English for Specific Purposes (ESP), traditional methods, educational technology, blended learning, personalized instruction, interactive learning, digital tools, resource constraints, digital literacy, assessment methods.